Molecular and crystal structure of Di(μ-N,S-thiocyanato)-bis[(N,N-dimethylbenzylamine-C2, N)palladium(II)] - Mauro, Antonio Eduardo [UNESP]; Netto, Adelino V.G. [UNESP]; Moro, Antonio C. [UNESP]; Ferreira, Janaina G. [UNESP]; Santos, Regina H.A.; de Almeida, Eduardo T. (Japan Society for Analytical Chemistry, 2009)
The cyclopalladated complex [Pd(C2,N-dmba)(μ-SCN)]2, where dmba = N,N-dimethylbenzylamine, was structurally characterized by single-crystal X-ray diffraction. This compound crystallizes in the monoclinic system, space group P21/n with a = 9.578(1)Å, b = 12.323(2)Å, c = 10.279(2)Å, β = 117.03(1)°, V = 1080.7(3)Å3, Z = 2. Each Pd(II) center displays a distorted square-planar coordination environment, formed by the C and N atoms from the dmba ligand, and one set of N and S atoms from the bridging SCN groups. 2009 © The Japan Society for Analytical Chemistry.